Akibat Hukum dari Perceraian dengan Alasan Istri Murtad: Studi di Pengadilan Agama Sleman - Hasyarania Hasyarania; Nurjihad Nurjihad (Jurnal Hukum dan Sosial Politik, 2025)
Marriage is the only way to legalize the relationship between men and women in order to realize the happiness of family life. Marriage is also a complement to the religion of Muslims. However, because marriage basically unites two different individuals, it certainly does not rule out the possibility of differences of opinion and other problems. Divorce is the last resort for a marital relationship that can no longer be maintained, divorce can occur for several reasons, including because the couple has changed religions, as contained in the Compilation of Islamic Law Article 116 letter H. Divorce certainly causes a legal consequence, one of which is the effect on children. If the divorce occurs because the wife or a mother has changed, then how is the determination of custody of a child who has not been mumayyiz. The purpose of this study is to find out the judge's considerations in determining child custody due to divorce because the couple changed religion in the decision Number 1515/Pdt.G/2015/PA.Smn. This research is a normative-empirical legal research, this research data uses secondary data consisting of primary, secondary and tertiary legal materials. To complete the secondary data, interviews were also conducted with the judge at the Sleman Religious Court. Based on the results of the research and analysis that has been carried out, it can be concluded that the judge's consideration in deciding the case of determining child custody due to divorce caused by a couple converting (apostasy) at the Sleman Religious Court was given to the Applicant as his father in order to maintain the safety of his child's faith and the best interests for his child and for the sake of the child's future.